A Comparative Study of Interleukin 6, Inflammatory Markers, Ferritin, and Hematological Profile in Rheumatoid Arthritis Patients with Anemia of Chronic Disease and Iron Deficiency Anemia - Eman Tariq Ali; Azza Sajed Jabbar; Ali Nazar Mohammed (Anemia)
Background. Interleukin-6 (IL-6) proinflammatory cytokine is associated with the pathogenesis of rheumatoid arthritis and development of anemia in it. This is a comparative study of inflammatory and hematological parameters in RA patients with anemia of chronic disease (ACD) and iron deficiency anemia (IDA). It aimed to demonstrate the changes in serum level of IL-6, ferritin level, and hematological parameters in different groups of patients with RA and to find out the potential correlation between serum level of IL-6 and ferritin level and the relationship between serum level of IL-6 and iron status. Methods. The study included 89 patients from both sexes divided into four groups (group 1: 30 iron deficiency anemia (IDA), 59 RA; group 2: 20 RA-COMBI; group 3: 23 RA-ACD; and group 4: 16 nonanemic RA). These different groups were compared with a healthy group of 50 healthy individuals. Different blood parameters (WBC, RBC, HGB, HCT, MCV, and MCH) have been evaluated. Serum concentrations of IL-6, hsCRP, anti-CCP, and ferritin were measured in all patients and healthy individual using enzyme-linked immunosorbent assay ELISA. Results. There were significant changes in most of blood parameters between the groups, and there was a significant increase in the levels of IL-6 among RA patients. This increase was highly significant among RA-ACD patients in particular, and this elevation has been directly correlated with clinical indices of disease activity such as hsCRP, ESR, anti-CCP, and ferritin. There was an inverse relationship between ferritin and all iron status parameter, such as RBC, HGB, and haematocrit. Conclusion. IL-6 and ferritin level estimation may be workable tests to differentiate the patients with IDA and ACD in RA.